Study of the VRF/VRV Air Conditioning System in the Hospital: A Review of Economic and Environmental Aspects - Arfidian Rachman; Lisa Nesti; Asmara Yanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2022)
Heating, ventilation and air cooling (HVAC) systems are the largest users of electrical energy in the hospital. The results showed that hospitals represent about 60% of the total energy consumption in the utility building sector. In this paper, it is presented about energy efficiency and the potential for energy savings in HVAC systems in hospitals. Conditioning systems with Variable Refrigerant Flow (VRF) or Variable Refrigerant Volume (VRV) Technology allow for greater energy efficiency and cost savings compared to traditional HVAC systems.